Secondary urban STEM teacher candidates’ perceptions of the impact of a culturally responsive classroom management course - McIntush, Karen Graham; Mateer, Ramona Mateer; Paige K. Evans (American Journal of STEM Education, 2025)
The research goal was to examine the impact of a culturally responsive classroom management (CRCM) course taken concurrently with clinical teaching on the development of secondary STEM teacher candidates’ CRCM self-efficacy in a UTeach program. The teacher candidates (n = 16) attended a Tier 1 research university in a diverse urban setting. The Culturally Responsive Classroom Management Self-Efficacy scale was administered as a pre/posttest (Siwatu, 2017), followed by an exit interview. Clinical teachers have demonstrated improved self-efficacy in areas such as developing student-teacher relationships to foster community, establishing co-created norms, and enforcing routines and procedures. The implications highlight the need to integrate CRCM in UTeach and STEM teacher preparation programs to promote inclusive, equitable STEM classrooms.